Effect of Corporate Governance on Performance of SACCOs in Rubanda District South Western Uganda - Turyasingura, John Bosco; Moses, Agaba (International Journal of Current Science Research and Review, 2023)
The goal of this study was to evaluate the effect of corporate governance on the performance of SACCOs, in Rukiga District. SACCO governance was a predictor variable and performance of SACCOs was the study's outcome variables. A cross sectional survey was the precursor to the study. Quantitative and qualitative analysis were combined with the collection and analysis of data from 109 respondents. Descriptive, bivariate, and multivariate analyses were used in the analysis, which was done on three different levels. Frequency tables were employed to portray the data as descriptive analysis required presentation of a single variable and its characteristics. A Pearson correlation matrix was used to determine the correlations between the predictor factors and the dependent variable at the bivariate level. The modified predictor variables for corporate governance were regressed against the dependent variable at the multivariate level (performance of SACCOs). To fit the data, a linear regression model was employed. Corporate governance (coef. = 0. 532) has a positive influence on the performance of SACCO in Rukiga District, according to research results from the regression model. The key finding of this study is that corporate governance significantly affects SACCOS performance. The study therefore suggests that in order to ensure the sustainability of SACCO performance in Rubanda District, greater emphasis should be placed on implementing corporate governance.